Biodiversity and distribution of the southern African sea cucumbers (Echinodermata: Holothuroidea) - Thandar, Ahmed S. (Zootaxa, 2015)
The history of the southern African holothuroid fauna south of the tropic of Capricorn, is updated and the biodiversity and distribution of the fauna discussed. All five currently recognized orders are represented, distributed over 24 families, 74 genera and 163 species. As many as 117 species are shelf forms comprising the following faunistic components : 36% Indo-Pacific, 12% West Indian Ocean, 1% Atlantic and 51% endemic. Four faunistic provinces are recognized : tropical Indo-Pacific Province on the east coast, extending to St Lucia in northern KwaZulu-Natal; the Subtropical (Natal) province, from this point to Port St. Johns in the Eastern Cape Province; the Warm Temperate (Agulhas) Province from this point to Cape Point in the Western Cape Province; and the Cold Temperate (Namaqua) from Cape Point to Walvis Bay in Namibia. Vertical distribution of the approximately 90 species collected from more than one locality is also given. The origin of the holothuroid fauna is briefly discussed and reiterated that the Indo-Pacific component moved in from the north mostly by way of the Mozambique-Agulhas Current. The origin of the endemic component is obscure but surmised that it is perhaps also of Indo-Pacific origin with negligible contribution from the Atlantic.